2017
DOI: 10.18805/ijar.v0iof.7004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sex on growth performance, nutrient utilizationand carcass characteristics in cross bred pigs

Abstract: A study was carried on 24 piglets (Large White York Shire × Desi) of an average initial weight of 20 kg of three gender groups, barrows, boars and gilts consisted of eight pigs each, of comparable body weight fattened from 20-48 kilograms (growing) to 49-96 kilograms (finishing) to see the effect of gender on growth performance, nutrient utilization and carcass traits. When comparing feed intake at the growing stage, gilts consumed significantly more (P<0.05) feed than boars and barrows. There was no significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Also, the drip loss values were lower, which is in accordance with the statement that a lower drip loss is related to higher pH values [30]. Muhlisin et al [34] found more stable pH 24 (5.62 vs. 5.56) and a lower drip loss in Korean Native Black pigs than in their hybrids with Duroc. This trend was also observed in the Japanese breed of Agu and the Large White × Landrace × Duroc hybrid (pH 48 5.61 vs. 5.53; drip loss 2.03% vs. 2.75%) [30].…”
Section: Physical and Chemical Characteristics Of Musculus Longissimus Lumborum Et Thoracissupporting
confidence: 86%
See 1 more Smart Citation
“…Also, the drip loss values were lower, which is in accordance with the statement that a lower drip loss is related to higher pH values [30]. Muhlisin et al [34] found more stable pH 24 (5.62 vs. 5.56) and a lower drip loss in Korean Native Black pigs than in their hybrids with Duroc. This trend was also observed in the Japanese breed of Agu and the Large White × Landrace × Duroc hybrid (pH 48 5.61 vs. 5.53; drip loss 2.03% vs. 2.75%) [30].…”
Section: Physical and Chemical Characteristics Of Musculus Longissimus Lumborum Et Thoracissupporting
confidence: 86%
“…Our findings are in accordance with other studies [5,23] where a significantly higher growth intensity was found in barrows than in gilts. For example, following the same breeding principles and age of pigs at slaughter, Peinado et al [23] reported a higher ADG in barrows than in gilts, by 113 g. However, in a significant number of studies, the differences in growth intensity between sexes are not so pronounced, in fact, they are often negligible, which suggests that this characteristic can differ depending on various factors, such as breeding systems, feeding strategies as well as genetic effects [24][25][26].…”
Section: Performance Parameters In Pigsmentioning
confidence: 99%
“…Gilts showed higher AID and ATTD of CP, CF, and ash, as well as for AID of several amino acids, compared to barrows. Higher ATTD of CP in gilts is previously reported by [59], including a nonsigni cant increase in ATTD of ether extract. The use of wood shavings as bedding material also increased the numerical ATTD except for NDF.…”
Section: Discussionmentioning
confidence: 56%
“…Even so, Ref. [17] did not find differences in ADG between barrows, boars, and gilts during the phases of growing (from 20 to 48 kg) and finishing (from 49 to 96 kg).…”
Section: Effect Of Sex On Growthmentioning
confidence: 82%
“…The authors of [16] studied the influence of sex on growth before birth and found that male conceptuses grew faster than female conceptuses before the attachment to the uterine lining. Other authors such as [17] found that sex had no significant effect on evisceration weight, dressing percentage and carcass length in adult pigs. However, there is scarce information available on the influence of sex on piglet growth during the postweaning phase (6-20 kg BW), which is common in countries like Spain.…”
Section: Introductionmentioning
confidence: 84%